Economic Growth Determinants Model Semarang City Year 2005 – 2017 - Aprih Santoso (INDEF - Institute for Development of Economics and Finance, 2020)
The purpose of this research was to analyze the effect of the Contribution of Regional Revenue (PAD) and General Allocation Grant (DAU) to Economic Growth (PDRB) of Semarang City through Capital Expenditure (BM). The data used in this research secondary data. The variables of this research consisted of Contribution of Regional Revenue (PAD), General Allocation Grant (DAU) as independent variables. Economic Growth (PDRB) as the dependent variable and the Capital Expenditure (BM) as an intervening variable. The test results and analysis of the data it can be concluded that the Contribution of Regional Revenue (PAD) and General Allocation Grant (DAU) directly effect on Economic Growth (PDRB) and Capital Expenditure (BM). and Capital Expenditure (BM) directly effect on Economic Growth (PDRB). Keywords: Revenue, Capital, Economic